Beliefs of English Language Instruction by Indonesian Elementary School Teachers: Exploring the Influence of Environment and Educational Background - Alpino Susanto; Sri Langgeng Ratnasari; Ervin Nora Susanti; Suswanto Ismadi Megah; Eka Wilany; Sri Yuliani (STAI Hubbulwathan Duri, 2024)
One of the reasons for the success of the teaching and learning process in the classroom is the teacher's belief system. Belief guides one’s thinking, action, and understanding of events. The level of beliefs in the teaching process needs to be probed before teachers critically manifest their teaching practices and facilitate outcome changes. In Indonesia, the independent curriculum (Kurikulum Merdeka), which was regulated in 2022, directs the teaching English since elementary school. The present study aims to assess the teachers' belief system in teaching English to elementary school students as the “Kurikulum Merdeka”implementation spirit. The study involved 32 English teachers. The questionnaire assessed the teachers' beliefs about teaching English to elementary school students in 3 areas: the nature of children's English development, methods and techniques, and self-efficacy. There was also 1 open-ended question addressed to teachers to investigate their level of beliefs in teaching English among elementary school students. Data analysis is described in the form of descriptive statistics, independent t-test analysis, and content analysis. The results of this study indicate that the international school environment has a better level of belief than the national-plus school. Meanwhile, there was no difference in the level of belief in teaching among teachers with different educational backgrounds when they were in college.